Social issue as an area of non-financial reporting in Poland on the example of selected companies listed on the Warsaw Stock Exchange - Czaja-Cieszyńska, Hanna (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The dissemination of the concept of sustainable development has resulted in the social issue becoming an important area of non-financial reporting. However, the complexity and multidimensionality of this category mean that the indicators used for this are very diverse. The literature on this subject includes numerous publications, but there is lack of answer to the question: are the social category disclosures presented in non-financial reports comparable? Aim: The aim of the paper is an assessment of the comparability of non-financial disclosures in the social area in reports of selected companies listed on the Warsaw Stock Exchange. The ten largest companies listed in the WIG-20 index were selected for the study. The study covered non-financial reports for 2019. The study was divided into five categories: (I) Human Rights, (II) Local Communities and Community Engagement, (III) Supplier Social Assessment, (IV) Customer Privacy, and (V) Other, within each, based on GRI Standards, up to three non-financial indicators have been defined. Results: The conducted empirical study confirmed that the analysed non-financial reports were not fully comparable in any of the five categories of disclosures. Moreover, in many reports verbal description dominated, with a relatively small share of information expressed in numbers and/or percentages, which in turn creates a field for narration. Non-financial reporting requires an appropriate balance between descriptive reporting and quantified information. This also applies to the disclosure of information on social issues. In this light, it seems necessary to lobby and then start legislative work aimed at increasing the comparability of non-financial reports.